Psychological Support in the Midst of VUCA Situations for Generation Z in the Finnish Education System - Latipah, Eva (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to identify the forms of psychological support provided by the Finnish education system to Generation Z in facing VUCA situations and analyze the strategies applied within the Finnish education system to strengthen the psychological resilience and adaptability of Generation Z in the VUCA era. Design/method/approach – The research uses a descriptive qualitative design to thoroughly describe the forms of psychological support and strategies applied within the Finnish education system. Data collection is conducted through in-depth interviews with teachers, school counselors, and education policymakers to explore their perspectives on the forms of support and strategies in place; participatory observation involving direct observation in schools to understand how psychological support is implemented in real educational settings; and documentation by analyzing Finnish education policy documents related to psychological support, learning guidelines, and student development programs. Data analysis is carried out thematically by identifying key themes related to forms of support and strategies relevant to supporting Generation Z in the VUCA era. Findings – The findings reveal that: 1) The psychological support provided includes: a) emotional support through an individualized approach to understand each student's emotional needs; b) social support in the form of collaborative group activities to help students overcome social isolation; and c) mental and health support through life skills programs to strengthen students' mental resilience. 2) The strategies used include a) proactive strategies with curriculum integration to train emotional-adaptation skills and the use of technology to create a flexible and personalized learning environment; b) responsive strategies through regular monitoring and evaluation of students' mental health via surveys and interviews; and c) holistic strategies involving a Finland-specific cultural approach emphasizing work-life balance and a national education policy prioritizing student well-being.